Weighted Renyi's entropy for lifetime distributions. Issue 14 (18th July 2017) - Nourbakhsh, Mohammadreza; Yari, Gholamhoseein
ABSTRACT: Recently, Di Crescenzo and Longobardi (2006 ) have studied "length-biased" shift-dependent information measure and its dynamic versions. On the other hand, Renyi's entropy plays a vital role in the literature of information theory that is a generalization of Shannon's entropy. In this article, the concepts of weighted Renyi's entropy, weighted residual Renyi's entropy, and weighted past Renyi's entropy are introduced and their properties are discussed.